Primary thyroid MALToma– a rare diagnosis of an unassuming thyroid nodule. Issue 1 (2nd January 2018) - Shrestha, Pragya; Aderhold, Kimberly; Swierczynski, Sharon; Lin, Catherine; Herb, Ronald
ABSTRACT: Primary thyroid lymphoma, although a rare malignancy, can arise in common chronic inflammatory conditions such as Hashimoto's thyroiditis. Incidental finding of a thyroid nodule with chronic thyroid inflammation warrants further investigation. Early detection of malignancy can play a vital role in improved outcomes. We report a case of a 60-year-old male who presented to the clinic for a routine visit. An enlarged, firm, non-tender thyroid gland was appreciated on exam with high thyroid stimulating hormone (TSH) level. Fine needle aspiration of the mass revealed nonspecific atypical lymphocytes. The pathology and immunohistochemical stains were consistent with histologic impression of extra nodal marginal B-cell lymphoma (mucosa-associated lymphoid tissue [MALT] lymphoma) and Hashimoto's thyroiditis. Patient was treated with thyroxine after complete surgical excision of left thyroid lobe and remains in remission with close follow-up with his primary care provider. Primary thyroid MALT lymphoma follows an indolent process and remains asymptomatic in most patients. These are usually found to arise at sites of ongoing chronic inflammation with underlying autoimmune or infectious etiologies. Treatment modalities include surgical excision and/or radiation therapy for localized lesions, with both radiation and chemotherapy indicated for disseminated disease.